The logarithmic Cauchy quotient mean. Issue 5 (3rd May 2020) - Himmel, Martin; Matkowski, Janusz
Abstract : Motivated by recent results on beta-type functions, a new family of means, which are of logarithmic Cauchy quotient type, are determined and characterized.